Childhood socioeconomic status interacts with cognitive function to impact scam susceptibility among community-dwelling older adults. (3rd April 2023) - Glover, Crystal M.; Yu, Lei; Stewart, Christopher C.; Wilson, Robert S.; Bennett, David A.; Lamar, Melissa; Boyle, Patricia A.
Abstract: Objectives: We examined whether childhood socioeconomic status (SES) is related to scam susceptibility in old age and tested the hypothesis that childhood SES interacts with cognitive function to impact scam susceptibility. Methods: This study employed a cross-sectional design. All data were collected in participants' community-based residences. Participants were 1071 older adults (mean age = 81.05 years, SD = 7.53) without dementia (median MMSE score = 28.29, IQR = 27.86–30.00). Participants completed assessments of childhood SES, cognitive function, and scam susceptibility. We used linear regression models to examine the associations of childhood SES and cognitive function with scam susceptibility. Results: In a regression model adjusted for age, gender, and education, poorer cognitive function was associated with higher scam susceptibility, but childhood SES was not. However, in an additional model that included the interaction of childhood SES and cognitive function, the interaction was significant, such that lower childhood SES was associated with higher scam susceptibility among participants with lower cognitive function. Conclusion: Lower childhood SES is associated with higher scam susceptibility among older adults with lower levels of cognitive function. Thus, older adults who experienced limited resources in childhood and have lower cognitive function may represent a specific group for interventions to increase scam awareness and prevent financial exploitation.